Multiple and flexible roles of facultative anaerobic bacteria in microaerophilic oleate degradation - Duarte, Maria Salomé (2020)
Anaerobic degradation of longchain fatty acids (LCFA) involves syntrophic bacteria and methanogens, but facultative anaerobic bacteria (FAB) might have a relevant role as well. Here we investigated oleate degradation by a syntrophic synthetic coculture of Syntrophomonas zehnderi (Sz) and Methanobacterium formicicum (Mf) and FAB (two oleatedegrading Pseudomonas spp. I1 + I2). Sz + Mf were first cultivated in a continuous bioreactor under strict anaerobic conditions. Thereafter, I1 + I2 were inoculated and microaerophilic conditions were provided. Methane and acetate were the main degradation products by Sz + Mf in anaerobiosis, and by Sz + Mf + I1 + I2 in microaerophilic conditions. However, acetate production from oleate was higher in microaerophilic conditions (5% O2) with the four microorganisms together (0.41 ±0.07mmol d1) than in anaerobiosis with Sz + Mf (0.23 ±0.05mmol d1). Oleate degradation in batch assays was faster by Sz + Mf + I1 + I2 (under microaerophilic conditions) than by Sz + Mf alone (under strict anaerobic conditions). I1 + I2 were able to grow with oleate and with intermediates of oleate degradation (hydrogen, acetate and formate). This work highlights the importance of FAB, particularly Pseudomonas sp., in anaerobic reactors treating oleatebased wastewater, because they accelerate oleate conversion to methane, by protecting strict anaerobes from oxygen toxicity and also by acting as alternative hydrogen/formate and acetate scavengers for LCFAdegrading anaerobes.